Introduction of the Rapid Deployment Aortic Valve System Use in Elderly Patients With Endocarditis - Öner, Alper; Hemmer, Christoph; Alozie, Anthony; Löser, Benjamin; Dohmen, Pascal M. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Introduction: The rapid-deployment valve system (RDVS) was introduced to facility minimally invasive aortic valve replacement. In this study we evaluate the potential benefits of RDVS in elderly high-risk patients with endocarditis of the aortic valve. Materials and Methods: Since the introduction of RDVS in our institution in December 2017 through October 2021, EDWARDS INTUITY rapid-deployment prosthesis (Model 8300A, Edwards Lifesciences, Irvine, CA, USA) has been implanted in a total of 115 patients for different indications by a single surgeon. Out of one-hundred and fifteen cases of RDVS implantation, seven patients with a median age of 77 yrs. (range 62-84yrs.), suffered from active infective endocarditis of the aortic valve. The median EuroSCORE II of these highly selected patient cohort was 77 % (range 19-80%). Patient data were evaluated perioperatively including intra-operative data as well as in-hospital morbidity/mortality and follow-up after discharge from hospital. Results: Three patients underwent previous cardiac surgery. Concomitant procedures were performed in six patients including, ascending aorta replacement (n=3), mitral valve repair (n=1), pulmonary valve replacement (n=1), bypass surgery (n=1), left atrial appendix resection (n=1) and anterior mitral valve repair (n=1). Median aortic cross-clamp and cardiopulmonary bypass time was 56 min. (range 29-122 min.) and 81 min. (range 45 – 162 min.), respectively. Post-operative complications in these elderly high-risk patients were atrial fibrillation (n=3) and re-exploration for pericardial effusion (n=1). One pacemaker implantation was required on postoperative day 6 due to sick sinus syndrome. There was one in-hospital death (14%) and one during follow-up (14%). Conclusion: Rapid-deployment aortic valve system seems to be a viable option with acceptable morbidity and mortality in elderly high-risk patients with active infective endocarditis of the aortic valve.